STUDY ON THE INFLUENCE OF THE STRUCTURE PARAMETERS OF THE WOUND CYLINDRICAL HONEYCOMB ON THE ENERGY ABSORPTION CHARACTERISTICS - JIANG ShiHong; WANG ChengQiang; JIN Hui; WANG Lei; SUN WenYue; LI ZhiFei (Jixie qiangdu)
In order to study the influence of the structural parameters of the wound cylindrical honeycomb on the energy absorption characteristics, a finite element simulation model was first established. Then, using the controlled variable method, the influence of the side length of the corrugated sheet, the thickness of the corrugated sheet and the thickness of the flat sheet on the energy absorption characteristics of the honeycomb was systematically studied. Finally, the experiment is carried out and compared with the simulation results. The results show that as the side length of the corrugated sheet decreases, the thickness of the corrugated sheet and the thickness of the flat sheet increase, the average stress and volume ratio energy absorption of the honeycomb can be increased; reducing the side length of the corrugated sheet and increasing the thickness of the corrugated sheet can increase the mass specific energy absorption. The increase in the thickness of the flat sheet can reduce the mass specific energy absorption; the simulation model is accurate, and the results are in good agreement with the experimental results in the honeycomb deformation and energy absorption characteristics. This paper has done a more detailed study on the three parameters that affect the strength of the cylindrical honeycomb, which provides new ideas and theoretical support for the energy-absorbing components of the passive safety protection of rail transit.